EFFECT OF PHYSICAL ACTIVITY IN MODERN LIFESTYLE - Chakraborti, Shipra; Kumar, Ashok (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
There is a lack of physical activity in modern life. The recommended 30 minutes of moderate-intensity physical activity are really only completed by 35% of men and 24% of women at least five times each week. At all ages, men are typically more physically active than women, and both sexes see a noticeable drop in physical activity as they get older. Compared to adults, children are more active. Despite the fact that levels of physical activity in both adults and children have remained relatively stable recently, there is some evidence to suggest that occupational activity has declined since the 1990s, as well as a decline in active transportation to school and time spent in physical education classes. This has occurred at the same time that adult sports activity is on the rise (example: membership in fitness clubs). It is obvious that physical activity has advantages for people of all ages. Physical activity helps children's bones grow stronger and maintain energy balance, which lowers their risk of developing chronic diseases as adults. Also, it is crucial for establishing healthy living habits, social connection, and wellbeing.